2001
DOI: 10.1300/j115v20n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Computer Search Services Relative to Instruction Services

Abstract: To assess the quality and usefulness of one health sciences library's mediated computer search service, a survey was undertaken to determine satisfaction rates, why users do or do not use the service, and how useful the service is perceived to be in comparison to instructional service. Satisfaction rates were high, with users indicating librarian expertise and time/cost savings as the main reasons for using the service. Non-users indicated that they preferred to do their own searching, and many were unaware of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Previous surveys have revealed that most participants prefer search request forms that solicit an expected number of citations [13] and results that are delivered by a handheld device or web interface [3]. Other surveys have found that the timeliness of delivering search results is important to patrons [14] and that decreasing the number of returned citations while increasing relevance is an important area for improvement [13, 15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous surveys have revealed that most participants prefer search request forms that solicit an expected number of citations [13] and results that are delivered by a handheld device or web interface [3]. Other surveys have found that the timeliness of delivering search results is important to patrons [14] and that decreasing the number of returned citations while increasing relevance is an important area for improvement [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys have revealed that most participants prefer search request forms that solicit an expected number of citations [13] and results that are delivered by a handheld device or web interface [3]. Other surveys have found that the timeliness of delivering search results is important to patrons [14] and that decreasing the number of returned citations while increasing relevance is an important area for improvement [13, 15]. A recent study evaluating literature search services by auditing service metrics at a large health library system concluded that improvement is necessary in the areas of data collection by librarians (e.g., time spent and resources searched), service promotion, administration of user-satisfaction surveys, and overall service standards [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet and the World Wide Web from the mid‐1990s revolutionised end‐user searching by facilitating 24/7 access, anywhere 33,41,42 . Demand for mediated searches decreased 43 and health librarians tried to determine the value of search services that they continued to offer and determine reasons for use and non‐use 44 . Librarians spent more time conducting classes and individual consultations, developing electronic collections and managing information systems 41,43 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Barnett et al analyzed the results of 196 surveys of library users and non-users; they found that 31.7% of those surveyed felt that computer searching instruction was the most useful library reference service and that 81.7% had performed their own searches during the past twelve months. 6 The Medical Library Association Policy Statement, The Librarian's Role in the Provision of Consumer Health Information and Patient Edu-cation, states "patient education is a planned activity, initiated by a health professional, whose aim is to impart knowledge, attitudes and skills with the specific goal of changing behavior, increasing compliance with therapy and, thereby, improving health." The policy statement provides guidance on how consumer health librarians can play a critical role in this process by: (1) creating awareness for health professionals regarding the health information needs of consumers, (2) encouraging the inclusion of CHI services in CE Courses as appropriate and encouraging the development of new education tools to meet emerging needs, (3) presenting education programs for public and other librarians on the effective provision of CHI, and (4) providing educational programs for the general public on locating and evaluating health information.…”
Section: Introductionmentioning
confidence: 99%